2008
DOI: 10.1165/rcmb.2007-0050oc
|View full text |Cite
|
Sign up to set email alerts
|

Basal Cells of Differentiated Bronchial Epithelium Are More Susceptible to Rhinovirus Infection

Abstract: We used an in vitro model of differentiated tracheobronchial epithelium to analyze the susceptibility of different cell types to infection with rhinoviruses (RVs). Primary cells from control subjects were cultured in an air-liquid interface to form differentiated epithelia. Suprabasal and basal fractions were separated after trypsin digestion, and cell suspensions were infected with serotypes RV16 and RV1A. These cell fractions were analyzed for expression of viral capsid protein VP2 (flow cytometry), viral re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
131
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 152 publications
(140 citation statements)
references
References 46 publications
8
131
0
Order By: Relevance
“…However, a recent study reported that various types of differentiated bronchial epithelial cells differ in their susceptibility to RV infection (46). Whereas cells at the superficial layer were relatively resistant to RV infection, basal cells were more sensitive.…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent study reported that various types of differentiated bronchial epithelial cells differ in their susceptibility to RV infection (46). Whereas cells at the superficial layer were relatively resistant to RV infection, basal cells were more sensitive.…”
Section: Discussionmentioning
confidence: 99%
“…This may be because of their differential susceptibility to RV infection. Previously, basal undifferentiated airway epithelial cells have been shown to be more susceptible to RV than are suprabasal mucociliary-differentiated cells (15). This difference was attributed to higher expression of intercellular adhesion molecule (ICAM)-1, a receptor for major group RV in basal epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…RV has also been shown to delay wound closure in nonpolarizedundifferentiated bronchial epithelial cells (14). Furthermore, basal/undifferentiated cells, which are readily accessible after airway epithelial injury and during regeneration, are more susceptible to RV infection than are the suprabasal/differentiated cells (15). On the basis of the facts that RV readily infects basal epithelial cells (which are abundant in injured airway epithelium or epithelium showing basal cell hyperplasia) and causes delay in wound closure, we hypothesized that RV may interfere with the cell repolarization and normal renewal of injured/regenerating airway epithelial cells, leading to structurally and functionally abnormal airway epithelium.…”
Section: Clinical Relevancementioning
confidence: 99%
“…Viral infections could damage the barrier function of the airway epithelium, leading to enhanced absorption of allergens and/or irritants across the airway wall and enhanced inflammation (98). Conversely, intact epithelial layers are difficult to infect with HRV in vitro, and replication is enhanced by damaging the epithelium or by removing the top layer of cells (41,68). These findings suggest that allergens and pollutants that damage airway epithelium could increase susceptibility to infection and/or lead to more-severe infections (Fig.…”
Section: Risk Factors For More-severe Hrv Illnessesmentioning
confidence: 99%